Welfare against growth gains in post-transition countries: What are the consequences for stability? - Maria Lissowska (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper discusses the underpinnings of the financial crisis of the last decade in post-transition countries. It explores the endogenous reasons of this crisis, and in particular a possible link between delayed and unequal growth of household incomes on the one hand and the instability of the growth and depth of recession after the financial crisis on the other. It indicates possible factors underpinning the rapidly growing indebtedness of households, enabling faster, but unsustainable growth in consumption. Furthermore, it claims also that the artificially boosted growth of consumption and a favourable proportion between wages and profits could attract investment (also FDI), possibly searching for short-term gains. It underlines that while the inflow of financial funds was the major reason for unstable growth in this region, endogenous factors also contributed.
Keywords: I38; J48; P51; 330; Welfare; post-transition economies; crisis; stability